The 'multilayer' theory of Denonvilliers' fascia: anatomical dissection of cadavers with the aim to improve neurovascular bundle preservation during rectal mobilization. (16th October 2019) - Ghareeb, W. M.; Wang, X.; Chi, P.; Wang, W.
Abstract: Aim: Denonvilliers' fascia is thought to be a multilayered fascial structure, based on its embryological development with the neurovascular bundle embedded within it. Recently, this theory had been proven histologically and by confocal microscopy in many published articles. However, the literature does not report on how surgeons can identify these structures. We aimed to determine the optimal surgical approach for preserving these critical structures. Method: Eighteen cadavers (13 male/five female) were included and treated according to the ethical considerations stated in the donation consent of our institution. Dissection was performed with the assistance of binocular loupes for better anatomical detail. The compositions of the prerectal fascia and the neurovascular bundle were observed and recorded at different levels of dissection using a high‐definition camera. Results: The theoretical multilayered fascia was found in male specimens as three fascial layers originating from the perineal body, seminal vesicles and posterior bladder neck. The first layer merged posterolaterally and fused with the rectosacral fascia (Waldeyer's fascia). The neurovascular bundle in male specimens was observed piercing the second and third layers, while the first layer acted as a protective cover. Dissection of female specimens demonstrated only one layer in the prerectal space. Conclusion: Intiating anterior rectal mobilization by incising the peritoneum posterior to its reflection seems to be anatomically correct to preserve DVF. However, its applicability may be difficult in a narrow chanllenging pelvis. The lateral rectal ligaments and Waldeyer's fascia should be dissected from their attachments to the proper fascia of the rectum.